Migration Decisions, Acculturation, and Overweight among Asian and Latino Immigrant Adults in the United States. Issue 3 (September 2016) - Gorman, Bridget K.; Novoa, Cynthia; Kimbro, Rachel Tolbert
Using the 2002–2003 National Latino and Asian American Study (NLAAS), we examine relationships between acculturation, migration decisions, and overweight among Latino and Asian immigrants. Pooled logistic regression models showed no evidence that acculturation and migration decisions were related to overweight among Asians, but models for Latinos indicated that aspects of acculturation (duration of US residence and English proficiency) and migration decisions (moving to find a job) were significantly associated with overweight status. However, interaction models also highlighted the gendered nature of the acculturation–weight relationship, such that country-of-origin ties can have different implications for the overweight status of male and female immigrants.